Upaya Peningkatkan Daya Saing Pasar Sambilegi Melawan Toko Modern Berjejaring di Kabupaten Sleman - Ayu Restianti; Nasrudin Muzakki (Empower : Jurnal Pengembangan Masyarakat Islam, 2023)
Sambilegi Market is a traditional market located in Sleman Regency, Yogyakarta. The presence of modern network stores that are growing rapidly in Sleman Regency also threatens traditional market traders and creates intense competition. Therefore, the Sambilegi Market traders association needs efforts to increase competitiveness against networked modern shops in Sleman Regency through a SWOT analysis. The purpose of this study is to describe efforts to increase the competitiveness of Sambilegi Market against networked modern stores in Sleman Regency through SWOT analysis and to describe the results of these efforts. This research method uses descriptive qualitative. Informant withdrawal techniques using purposive techniques based on criteria. In addition, the data collection techniques used are observation, interviews, and documentation. All data were analyzed through the process of data reduction, data presentation, and drawing conclusions. The results of this study indicate that efforts to increase the competitiveness of Sambilegi Market against networked modern shops in Sleman Regency through SWOT analysis include: 1) Strengthening market institutions through providing capital to traders who need capital; procuring mass gymnastics for consumers, so that the relationship between buyers or customers and Pasar Sambilegi traders remains harmonious; take care of each trader's customers; and there is cooperation between the Department of Industry and Trade and the Sambilegi Market Association. 2) Increased human resource capacity, such as Sambilegi Market being able to compete with modern shops because Sambilegi Market traders are able to present products obtained directly from farmers and sell them at affordable prices to buyers; the awareness of several Sambilegi Market traders starting to promote their wares at Sambilegi Market via WhatsApp and Facebook status; the idea of joint wholesalers from the Sambilegi Market Association and the People's Market School emerged, although this has not yet been realized.